2007
DOI: 10.1051/forest:2006106
|View full text |Cite
|
Sign up to set email alerts
|

Les assemblages de macro-invertébrés détritivores du sol d’une rotation de futaie de hêtre

Abstract: -This work addresses the driving factors responsible for patterns in the detritivore macrofaunal communities of a managed beechwood chronosequence (28 to 197 years old, Normandy, France). We investigated the variation patterns of density, biomass and diversities of detritivore macrofauna throughout this rotation. Multivariate analyses were carried out to identify the main covariation patterns between species and some properties of their physical environment, and to describe the main ecological gradients constr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 35 publications
1
22
1
Order By: Relevance
“…These results confirms the previous studies conducted on a temperate cool rain forest in west Canada where there were no significant differences in population density of arthropods between undisturbed forests on harvested plots and unharvested patches (Addison 2007). Additionally, in another recent study, regarding a beech forest, the hypothesis of Ponge et al (1998), which predicts community changes during forest rotations, was refuted from a functional view point (Hedde et al 2007). However several studies considering the effects of silvicultural practices on soil fauna found important impacts on soil forest fertility/productivity and in the terrestrial food chain (Moore et al 2002).…”
Section: Qbs-ar and Forest Composition/managementmentioning
confidence: 99%
See 1 more Smart Citation
“…These results confirms the previous studies conducted on a temperate cool rain forest in west Canada where there were no significant differences in population density of arthropods between undisturbed forests on harvested plots and unharvested patches (Addison 2007). Additionally, in another recent study, regarding a beech forest, the hypothesis of Ponge et al (1998), which predicts community changes during forest rotations, was refuted from a functional view point (Hedde et al 2007). However several studies considering the effects of silvicultural practices on soil fauna found important impacts on soil forest fertility/productivity and in the terrestrial food chain (Moore et al 2002).…”
Section: Qbs-ar and Forest Composition/managementmentioning
confidence: 99%
“…Various studies have described the structure of soil invertebrate communities in relation to forest diversity, dynamics and management (Bird et al 2000;DoblasMiranda et al 2007;Hedde et al 2007;Jabin et al 2004;Kaneko and Salamanca 1999;Paquin and Coderre 1997;Theenhaus and Schaefer 1995). Overexploitation generally results in dramatic and rapid changes in vegetation and soil quality that are likely to significantly affect soil invertebrate communities and, more in general, forest goods and services (Minnesota Forest Resources Council 1999).…”
mentioning
confidence: 99%
“…This may occur through mass flow or through direct transport by soil fauna (Chamberlain et al, 2006). Soil faunal communities in these acidic stands are characterised by a lack of soil-dwelling earthworms and a low biomass of the detritivore macrofauna in the whole rotation (Hedde et al, 2007). On the other hand, strong variations in the density of detritivore mesofauna (enchytraeides, oribatide mites and springtails) were recorded between the different phases (Hedde, unpublished data), suggesting that these groups may be implicated in SOM vertical transport.…”
Section: Om Dynamics In Humic Epipedonmentioning
confidence: 99%
“…Habitat preferences or dispersal limitations 554 may prevent the recolonization of these stenotopic forest ground 555 beetle species in the reforested stands (Niemelä et al, 1993;556 Magura et al, 2003;Pohl et al, 2007 (Desender et al, 1999;Toïgo et al, 2013;Skłodowski, 2014a;561 Negro et al, 2014). These conditions are more commonly met in logging is practiced (Desender et al, 1999 (Hedde et al, 2007). However, samples from the youngest stages…”
mentioning
confidence: 99%